THE WHEELCHAIR AS A SIGN OF MOTOR DISABILITY: A PHENOMENOLOGICALLY GROUNDED SOCIOLOGICAL PERSPECTIVE - Viluckienė, Jolita (Sociologija. Mintis ir veiksmas, 2012)
The article applies Alfred Schutz’s phenomenologically grounded sociological perspective to explore how people in wheelchairs construct and maintain their significant social reality through subjective meanings, one of the key elements of everyday life being the wheelchair itself. Their personal narratives are based on qualitative in-depth interviews and suggest that due to the different schemes of interpretation applied towards ‘reading’ the same sign – in this case the wheelchair – different individuals assign different meanings, which to them signify different realities. This variety of meanings given to the wheelchair depends on the stock of social knowledge available to each person with a disability, which includes the cultural and symbolic meanings of disability that prevail in a society, as well as the type of disability – congenital or injury-/illnessacquired. The meanings also vary based on personal experience of interactions with other disabled people prior to injury, or on a lack of such experience. Among people with disabilities, such factors (facets) are involved in the formation or adjustment of attitudes towards the wheelchair during the re-socialisation process.Keywords: motor disability, wheelchair, disabled, subjective meaning, phenomenological sociology.